2022
DOI: 10.1039/d2nr03935d
|View full text |Cite
|
Sign up to set email alerts
|

Self-trapped excitons in soft semiconductors

Abstract: Self-trapped excitons (STEs) have attracted tremendous attention due to their intriguing properties and potential optoelectronic applications. STEs are formed from the lattice distortion induced by the strong electron (exciton)-phonon coupling...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 231 publications
(454 reference statements)
0
26
0
Order By: Relevance
“…It should be noted that the FCP can be applied to crystalline solids when excitons self-localize and a strong electron–phonon coupling is present. , Evidence is emerging that conditions in TMD-based van der Waals heterostructures may be conducive to self-localized excitons, , raising the prospect that the free-excitons in WS 2 are self-trapping when forming the exciton–phonon bound state. Further research is required to determine the model that best describes the system.…”
Section: Resultsmentioning
confidence: 99%
“…It should be noted that the FCP can be applied to crystalline solids when excitons self-localize and a strong electron–phonon coupling is present. , Evidence is emerging that conditions in TMD-based van der Waals heterostructures may be conducive to self-localized excitons, , raising the prospect that the free-excitons in WS 2 are self-trapping when forming the exciton–phonon bound state. Further research is required to determine the model that best describes the system.…”
Section: Resultsmentioning
confidence: 99%
“…This property endows lead halide perovskite flexibility and controllability in synthesis. [9][10][11] Recently, the broadband emission exhibited in low-dimensional or doped perovskites has become a hot research topic, and a large number of single-component white light emitters have been reported. [12][13][14][15][16] The broadband emission originates from the lattice distortion in the excited state, leading to selftrapping excitons.…”
mentioning
confidence: 99%
“…It is primarily due to their remarkable properties, including a high absorption coefficient, impressive luminescence efficiency, and long carrier diffusion lengths. These optical and electrical properties can be effectively tuned by changing their chemical composition. As the chemical composition directly influences the dimensionality of perovskites, low-dimensional structures are easy to obtain by altering metal cations, mixing halide ions, and using long chain organic ligands. In low dimensional metal-halides, the strong lattice distortion induced by the pseudo-Jahn–Teller effect can enhance the electron–phonon interactions. Furthermore, since the charge carriers (excitons) are well confined, the exciton binding energy is large, leading to an efficient exciton radiative recombination and high photoluminescence quantum yield (PLQY). These unique characteristics of low-dimensional halide perovskites make them attractive for light-emitting diode (LED) applications. Especially, they can exhibit broadband emission with a large Stokes shift, rendering the possibility to achieve direct single-component white-light LEDs. …”
mentioning
confidence: 99%